The Impact of NLRP3 Inflammasome on Osteoblasts and Osteogenic Differentiation: A Literature Review - Yang Z; Xu J; Kang T; Chen X; Zhou C (Dove Medical Press, 2024)
Ziyuan Yang,1,2 Jiaan Xu,3 Ting Kang,1,2 Xuepeng Chen,1,2 Chengcong Zhou4 1Stomatology Hospital, School of Stomatology, Zhejiang University School of Medicine, Hangzhou, 310006, People's Republic of China; 2Clinical Research Center for Oral Diseases of Zhejiang Province, Key Laboratory of Oral Biomedical Research of Zhejiang Province, Cancer Center of Zhejiang University, Hangzhou, 310006, People's Republic of China; 3College of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 4The First Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of ChinaCorrespondence: Chengcong Zhou, The First Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People's Republic of China, Email 1092141931@qq.com Xuepeng Chen, Stomatology Hospital, School of Stomatology, Zhejiang University School of Medicine, 166 North Qiutao Road, Hangzhou, 310006, People's Republic of China, Email cxp1979@zju.edu.cnAbstract: Osteoblasts (OBs), which are a crucial type of bone cells, derive from bone marrow mesenchymal stem cells (MSCs). Accumulating evidence suggests inflammatory cytokines can inhibit the differentiation and proliferation of OBs, as well as interfere with their ability to synthesize bone matrix, under inflammatory conditions. NLRP3 inflammasome is closely associated with cellular pyroptosis, which can lead to excessive release of pro-inflammatory cytokines, causing tissue damage and inflammatory responses, however, the comprehensive roles of NLRP3 inflammasome in OBs and their differentiation have not been fully elucidated, making targeting NLRP3 inflammasome approaches to treat diseases related to OBs uncertain. In this review, we provide a summary of NLRP3 inflammasome activation and its impact on OBs. We highlight the significant roles of NLRP3 inflammasome in regulating OBs differentiation and function. Furthermore, current available strategies to affect OBs function and osteogenic differentiation targeting NLRP3 inflammasome are listed and analyzed. Finally, through the prospective discussion, we seek to provide novel insights into the crucial role of NLRP3 inflammasome in diseases related to OBs and offer valuable information for devising treatment strategies.Keywords: osteoblast, pyroptosis, NLRP3 inflammasome, osteogenic differentiation